2017
DOI: 10.21162/pakjas/17.3681
|View full text |Cite
|
Sign up to set email alerts
|

Sucrose Metabolism for Cellulose Biosynthesis in Colored Cotton Fibers

Abstract: Assays were conducted to examine the contents of cellulose and callose, and the activities of enzymes related to sucrose metabolism at various stages of fiber development in colored cottons and white cotton. The results showed that the cellulose accumulation could be described with Richard curve equations, and the cellulose biosynthesis was reflected by the eigenvalues, especially the maximum biosynthesis rate (Vmax) and the time taken for cellulose rapid biosynthesis (T). The period from 20 days post anthesis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 24 publications
1
4
0
Order By: Relevance
“…Thus, the cellulose content also can provide an indication of fiber quality (Dutt et al, 2004; Fan et al, 2013). This is also supported by the research of Yuan et al (2012) and Zhang et al (2017c) who reported that cellulose accumulation in colored cotton fiber increased in an S‐shaped curve, which was not asymmetric. It was assumed that during fiber development in colored cotton, the biosynthesis of pigment (which does not occur in white cotton fiber) affects the accumulation of cellulose.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…Thus, the cellulose content also can provide an indication of fiber quality (Dutt et al, 2004; Fan et al, 2013). This is also supported by the research of Yuan et al (2012) and Zhang et al (2017c) who reported that cellulose accumulation in colored cotton fiber increased in an S‐shaped curve, which was not asymmetric. It was assumed that during fiber development in colored cotton, the biosynthesis of pigment (which does not occur in white cotton fiber) affects the accumulation of cellulose.…”
Section: Discussionsupporting
confidence: 82%
“…The development of cotton fiber is a process of cellulose synthesis and cellulose accumulation. Research has indicated that a higher cellulose content in fiber cells provides for better cotton fiber quality (Pan et al, 2010; Zhang et al, 2017c). Our present work demonstrated that the contents of cellulose in brown and green cotton were both lower than in white cotton, and this may be the reason why fiber quality of colored cotton is inferior to white cotton (Table 1).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Colored cotton can reduce the bleaching and dyeing components of the textile process and potentially reduce environmental pollution. Therefore, since the colored cotton mutant was discovered, it has become the research focus [ 40 ]. At present, natural colors are limited to brown, green, and red [ 41 ].…”
Section: Results and Analysismentioning
confidence: 99%
“…The stiffness of pea cotyledons, whose cell walls are rich in galactose, is also significantly enhanced by pectin polysaccharides [ 13 ]. Nonstructural carbohydrates, such as sucrose, can promote the formation of cellulose [ 14 , 15 ], thereby increasing stem elasticity and lodging resistance [ 16 ]. Ishimaru et al [ 17 ] showed that higher starch content in the stems of rice varieties resulted in stronger stems.…”
Section: Introductionmentioning
confidence: 99%